Cascading Target Tracking Control in Wireless Camera Sensor and Actuator Networks. Issue 4 (24th May 2017) - Wang, Tian; Peng, Zhen; Xu, Wenzheng; Liang, Junbin; Wang, Guojun; Tian, Hui; Cai, Yiqiao; Chen, Yonghong
Abstract: Recent years have witnessed the fast development of camera sensor networks (CSNs), but most of the existing research methods are based on homogeneous CSNs, which are not cost‐effective and are hard to evolve from traditional wireless sensor networks (WSNs). In this paper, we focus on the target tracking problem in heterogeneous wireless camera sensor and actuator networks which consists of a large number of common static sensors and a small number of mobile camera sensors. The objective is to control camera sensors to track targets dependably with maximized effective monitoring time and short moving distance. We first design a novel tracking algorithm for tracking one target where multiple camera sensors cooperate with each other to track the target in a cascading scheme. Moreover, this cascading algorithm is extended for a multi‐target scenario in consideration of tracking performance and loading balance for multiple targets. The effectiveness of proposed control algorithms is validated by extensive simulation results, which show that they can achieve high monitoring efficiency and comparatively short moving distance.